In vitro Phosphorylation of the Focal Adhesion Targeting Domain of Focal Adhesion Kinase by Src Kinase - Cable, Jennifer (2012)
Focal adhesion kinase (FAK), a key regulator of cell adhesion and migration, is overexpressed in many types of cancer. The C-terminal focal adhesion targeting (FAT) domain of FAK is necessary for proper localization of FAK to focal adhesions and subsequent activation. Phosphorylation of Y926 in the FAT domain by the tyrosine kinase Src has been shown to promote metastasis and invasion in vivo by linking the FAT domain to the MAPK pathway via its interaction with Grb2. Several groups have reported that inherent conformational dynamics in the FAT domain likely regulate phosphorylation of Y926; however, what regulates these dynamics is unknown. In this paper, we demonstrate that there are two sites of in vitro Src-mediated phosphorylation in the FAT domain: Y926, which has been shown to affect FAK function in vivo, and Y1008, which has no known biological role. The phosphorylation of these two tyrosine residues is pH dependent, but this does not reflect the pH dependence of Src kinase activity. CD and NMR data indicate that the stability and conformational dynamics of the FAT domain are sensitive to changes in pH over a physiological pH range. In particular, regions of the FAT domain previously shown to regulate phosphorylation of Y926 as well as regions near Y1008 show pH-dependent dynamics on the μs-ms time scale.